Outbreak of powdery mildew caused by Sawadaea negundinis on boxelder in Iran. Issue 6 (26th July 2017) - Arzanlou, M.; Narmani, A.
Summary: Boxelder ( Acer negundo ) is planted as ornamental and shade tree in many countries including Iran. During July 2016, boxelder trees in parks and streets of different localities in East Azarbaijan province, Iran were found to be heavily infected with powdery mildew. Whitish powdery fungal mass developed mainly on the lower leaf surface. The infected young leaves became bubbled, curled and crinkled, giving affected plants an unpleasant appearance. During September, scattered, dark brown, spherical chasmothecia were produced on the lower leaf surface. The causal agent was identified as Sawadaea negundinis based on a combination of morphological characteristics of sexual and asexual morphs and sequence data of the rDNA internal transcribed spacer region (ITS1‐5.8S‐ITS2). This study provides the first report on the occurrence of S. negundinis on boxelder in Iran.